Pengaruh Motivasi Dan Disiplin Kerja Terhadap Kinerja Aparatur Desa Padungnyo Kecamatan Nambo: The Influence Of Motivation And Work Discipline On Performance Apparatus Padungnyo Nambo District - Sibay, Yusnita Fitarini; Ridwan; Vey Intadja, Anggita (Jurnal Ilmiah Produktif, 2023)
This research was conducted to determine and analyze the influence of motivation and work discipline on performance (Case Study on Village Apparatus in Padungnyo, Nambo District). The analytical method used in this research is multiple linier regression analysis using 8 samples. Based on the results of data processing with the help of the SPSS version 25 program, the multiple linear regression equation Y = 11.483 + 0.404X1 + 0.101X2 + e was obtained. The constant value is 11.483, means that if it is not influenced by the work motivation and work discipline variables, the performance will be 11.483. The variables of work motivation (X1), work discipline (X2) have a significant and positive influence on performance (Y). The correlation coefficient (r) of 0.675 or is in the interval 0.60 – 0.80, meaning that the relationship between the independent variables motivation and work discipline and the dependent variable performance has a strong relationship. The coefficient of determination (R) of 0.455 or 45.5% shows the percentage of influence or contribution of the independent variable in explaining the dependent variable, namely 45.5% and the rest is explained by variables other than the variable being tested. The results of the F test show that the variables of motivation and work discipline have a significant and positive effect on performance, with an Fcount of 2.088 and a Ftable of 4.46.